Behavior in social media use from maqasid al-Shari'ah perspective and values among IIUM students - Shompa, Zohora Azmin (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2020)
The use of social media has raised concern on users' ability to behave ethically in cyberspace. The various issues include in social media such as accuracy, privacy, security, respect, dignity and many others. Handling these issue lies in the person of using social media properly from the Islamic perspectives. Therefore, this paper aimed to examine the users' behavior in social media use from Maqasid al-Shari'ah perspective and to explore the values that influence the behavior in social media use. Furthermore, this study examines the relations between values and social media use among IIUM students as students from an Islamic institution. This study integrates the Schwartz's basic human values theory with distinctiveness of the 10 values to analyze how values influence the behavior in social media context. The present study utilized the mix research method to answer the research questions. In this study, the behavior in social media use from Maqasid al-Shari'ah perspective and proposed values were obtained through focus group discussion (FGD). A total of 250 respondents were selected through a stratified sampling and data were collected using self-administered questionnaire to determine whether values influence behavior in social media use. The hypothetical relationships were examined through multiple regression analysis (MRA).The findings show that Islamic values, personal values and core values are correlated significantly with social media use among IIUM students while universal and social values have found non-significant. The result of this study will aide in the development of discourse for Muslim to use social media from the Islamic perspective that will create awareness, promote safe and responsible use.